Self Foot Care sebagai Upaya Pencegahan Komplikasi Kaki Diabetik - Danuartha Vandika; Fahrun Nur Rosyid (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the effect of self foot care on preventing diabetic foot complications in patients with Diabetes Mellitus. The method used was a literature review study using the PubMed, ScienceDirect, Semantic Scholar, and Google Scholar databases for publications on “self foot care,” “diabetic foot ulcer,” “foot care,” and “diabetes mellitus” from 2022 to 2026. The results showed that there were 15 articles that met the inclusion criteria. A total of 8 articles used quantitative research methods, 2 articles used qualitative research methods, and 5 articles used literature review methods. Most studies showed that self foot care has a significant effect on preventing diabetic foot complications in patients with Diabetes Mellitus. Foot care education, routine foot examination, proper footwear use, and early detection of diabetic wounds were proven effective in reducing the risk of diabetic ulcers, peripheral neuropathy, and amputation. In conclusion, self foot care has a significant effect on preventing diabetic foot complications in patients with Diabetes Mellitus and can improve patients’ ability and adherence in performing independent foot care. Keywords: Diabetes Mellitus, Diabetic Foot Ulcer, Foot Care, Self Foot Care